Features of psychological condition of cancer patient’s relatives in different stages of treatment process - Мухаровська, Інна Романівна (ScienceRise: Medical Science, 2016)
The study of mental stress manifestation features of cancer patients’ relatives in different stages of treatment process. Contingent and methods. The research was carried out at Kyiv city clinical oncology center. According to informed consent, 218 cancer patients’ relatives participated in psychodiagnostic survey. Results. Psychological problems of cancer patients’ relatives dealt with the lack of information, personal emotions, interaction with patient, and involvement in the treatment process. Patient’s relatives showed different behavior models during the treatment process, namely hyper care, estrangement, and balanced contact. During primary antitumor treatment in cancer patient’s relatives, mental distress was due to the lack of information, and the lack of skills for counteracting stress, caused by their relative disease; repeated anticancer therapy period characterized by effective coping and adaptation to the situation formation; palliative stage characterized by tension repeated rise, and reorientation to a new strategy of help. Conclusion. Mental distress manifestation in cancer patients’ relatives pointed to the necessity of medical and psychological assistance for them